2019
DOI: 10.1002/jrs.5664
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced anharmonic phonon coupling and decay dominated by low‐energy phonons in CdS nanowires

Abstract: Low‐energy optical phonons with energy in the order of that of acoustic phonons are readily populated at room temperature, and therefore, they play a key role in thermal, electronic, and thermo‐electric fundamental processes in a solid material. High‐quality crystalline cadmium sulfide (CdS) nanowires with a diameter of several tens of nanometer and a length up to several micrometers (3–5 μm) demonstrate strong exciton–phonon coupling. This strong coupling interaction allows us to observe low‐energy optical ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…First-order LO phonons and their overtones 2LO were observed at 300.8 and 603.3 cm –1 . Besides the 1LO and 2LO phonon modes, several other Raman peaks were resolved at 211.4, 238.5, and 254.1 cm –1 , which can be assigned to 1LO-2 E 2 low multiphonon coupling mode, the TO phonon with A 1 symmetry, and E 2 high phonon mode ( E 2 low means the high energy E 2 symmetry mode, and E 2 low means the low energy E 2 symmetry mode) . The phonon modes found by the Raman spectrum in the CdS single crystal are listed in Table S3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First-order LO phonons and their overtones 2LO were observed at 300.8 and 603.3 cm –1 . Besides the 1LO and 2LO phonon modes, several other Raman peaks were resolved at 211.4, 238.5, and 254.1 cm –1 , which can be assigned to 1LO-2 E 2 low multiphonon coupling mode, the TO phonon with A 1 symmetry, and E 2 high phonon mode ( E 2 low means the high energy E 2 symmetry mode, and E 2 low means the low energy E 2 symmetry mode) . The phonon modes found by the Raman spectrum in the CdS single crystal are listed in Table S3.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the 1LO and 2LO phonon modes, several other Raman peaks were resolved at 211.4, 238.5, and 254.1 cm −1 , which can be assigned to 1LO-2E 2 low multiphonon coupling mode, the TO phonon with A 1 symmetry, and E 2 high phonon mode (E 2 low means the high energy E 2 symmetry mode, and E 2 low means the low energy E 2 symmetry mode). 63 The phonon modes found by the Raman spectrum in the CdS single crystal are listed in Table S3. The energy difference between two adjacent subpeaks in Figure 4 indicates the existence of four main optical phonon modes in the CdS single crystal, i.e., LO, TO, E 2 high , and E 2 low modes, with energies of 37, 30, 32, and 5.5 meV, respectively.…”
Section: Determination Of Hole Polaronsmentioning
confidence: 99%
“…6 4 n While the factor group theory predicts that Raman active modes are 1A 1 + 1E 1 + 2E 2 . As a result of wurtzite CdS's noncentrosymmetric structure, the A 1 and E 1 modes can further be subdivided into longitudinal optical (LO) and transverse optical (TO) modes [33,36]. The typical fundamental longitudinal optical (LO) phonon and its overtone (2LO) are detected at 299 and 599 cm −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Cadmium sulfide (CdS) is a vital n-type II-VI semiconductor with a 2.42 eV direct energy band gap [32,33]. CdS is one of the most suitable candidates for applications in optoelectronic devices because of the high transparency of its visible spectrum, improved photoconductivity, and facile ohmic contact with other materials [34].…”
Section: Introductionmentioning
confidence: 99%
“…They found enormous Raman yield enhancement from octahedral‐shaped nanocrystals over this broad spectral range. Iqbal et al [ 96 ] studied low‐energy phonons in CdS nanowires and found this vibrational region enhanced by anharmonic phonon coupling and decay. Their results show that low‐energy phonons (both optical and acoustical) dominate anharmonic phonon decay in CdS.…”
Section: Nanomaterialsmentioning
confidence: 99%